DOI: 10.33915/etd.6836
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and Spatial Distribution of Imidacloprid and the Arthropod Fauna Associated with Eastern Hemlock, Tsuga canadensis (L.) Carr

Abstract: Eastern hemlock, Tsuga canadensis (L.) Carr (Pinales: Pinaceae), is an important component of both the urban and forest landscape of the eastern United States. Eastern hemlock has been heavily impacted by the introduction of the hemlock woolly adelgid, Adelges tsugae (Annand) (Hemiptera: Adelgidae). Two goals of this research were (1) to determine the effect of treatment timing (spring versus fall) and application method (tree injection versus soil injection) on the spatial and temporal distribution of imidacl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 40 publications
(73 reference statements)
2
4
0
Order By: Relevance
“…This study found basal bark applications 52 produce imidacloprid and olefin tissue concentrations similar to those associated with soil injections. In addition, concentrations were similar to those found in other studies, despite different application methods (Turcotte 2015, Cowles and Lagalante 2009, Benton et al 2016.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…This study found basal bark applications 52 produce imidacloprid and olefin tissue concentrations similar to those associated with soil injections. In addition, concentrations were similar to those found in other studies, despite different application methods (Turcotte 2015, Cowles and Lagalante 2009, Benton et al 2016.…”
Section: Discussionsupporting
confidence: 88%
“…Research exploring the effects of imidacloprid applications on arthropods is contradictory. Of the 484 arthropods investigated by Turcotte (2015), no difference in mean population levels were found when compared to the untreated control. Dilling (2009) conducted in particular phyotophygus and transient insect communities.…”
Section: Non-target Organismsmentioning
confidence: 86%
See 2 more Smart Citations
“…To ensure all hemlock trees were A. tsugae free, stand-wide surveys of hemlock trees to check the presence of A. tsugae at each site were conducted in 2004–2006. In addition, bi-weekly visual surveys of the distal 45 cm of one randomly selected branches from each tree were conducted (ground level to ∼3 m above ground) on all study trees from May to October in 2005 and 2006 ( Costa 2005 , Costa and Onken 2006 , Turcotte 2016 ).…”
Section: Methodsmentioning
confidence: 99%